Size of Craniectomy Predicts Approach-Related Shear Bleeding in Poor-Grade Subarachnoid Hemorrhage - Martin Vychopen; Johannes Wach; Tim Lampmann; Harun Asoglu; Hartmut Vatter; Erdem Güresir (Brain Sciences, 2023)
Decompressive craniectomy is an option to decrease elevated intracranial pressure in poor-grade aneurysmal subarachnoid hemorrhage (SAH) patients. The aim of the present study was to analyze the size of the bone flap according to approach-related complications in patients with poor-grade SAH. We retrospectively analyzed poor-grade SAH patients (WFNS 4 and 5) who underwent aneurysm clipping and craniectomy (DC or ommitance of bone flap reinsertion). Postoperative CT scans were analyzed for approach-related tissue injury at the margin of the craniectomy (shear bleeding). The size of the bone flap was calculated using the De Bonis equation. Between 01/2012 and 01/2020, 67 poor-grade SAH patients underwent clipping and craniectomy at our institution. We found 14 patients with new shear bleeding lesion in postoperative CT scan. In patients with shear bleeding, the size of the bone flap was significantly smaller compared to patients without shear bleeding (102.1 ± 45.2 cm2 vs. 150.8 ± 37.43 cm2, p > 0.0001). However, we found no difference in mortality rates (10/14 vs. 23/53, p = 0.07) or number of implanted VP shunts (2/14 vs. 18/53, p = 0.2). We found no difference regarding modified Rankin Scale (mRS) 6 months postoperatively. In poor-grade aneurysmal SAH, the initial planning of DC—if deemed necessary —and enlargement of the flap size seems to decrease the rate of postoperatively developed shear bleeding lesions.